A study of measurement of noninvasive blood pressure with the oscillometric device, Sentinel, in isoflurane‐anaesthetized horses. (31st July 2014) - Hatz, Lea‐Annina; Hartnack, Sonja; Kümmerle, Jan; Hässig, Michael; Bettschart‐Wolfensberger, Regula
Abstract Objective To assess accuracy of noninvasive blood pressure (NIBP) measured by oscillometric device Sentinel compared to invasive blood pressure (IBP) in anaesthetized horses undergoing surgery. To assess if differences between the NIBP measured by the Sentinel and IBP are associated with recumbency, cuff placement, weight of the horse or acepromazine premedication and to describe usefulness of the Sentinel. Study design Prospective study examining replicates of simultaneous NIBP and IBP measurements. Animals Twenty‐nine horses. Methods Invasive blood pressure was measured via a catheter in the facial artery, transverse facial artery or metatarsal artery. NIBP was measured using appropriate size cuffs placed on one of two metacarpal or metatarsal bones or the tail in random order. With both techniques systolic (SAP), mean (MAP), and diastolic (DAP) arterial blood pressures and heart rates (HR) were recorded. A mixed effects model compared the IBP to the NIBP values and assessed potential effects of catheter placement, localisation of the cuffs in combination with recumbency, weight of the horse or acepromazine premedication. Results Noninvasive blood pressure yielded higher measurements than IBP. Agreement varied with recumbency and cuff position. Estimated mean differences between the two methods decreased from SAP (lateral recumbency: range −5.3 to −56.0 mmHg; dorsal recumbency: range 0.8 to −20.7 mmHg), to MAP (lateral recumbency: range −1.8 to −19.0 mmHg; dorsal recumbency: range 13.9 to −16.4 mmHg) to DAP (lateral recumbency: range 0.5 to −6.6 mmHg; dorsal recumbency: range 21.0 to −15.5 mmHg). NIBP measurement was approximately two times more variable than IBP measurement. No significant difference between IBP and NIBP due to horse's weight or acepromazine premedication was found. In 227 of 1047 (21.7%) measurements the Sentinel did not deliver a result. Conclusion and clinical relevance According to the high variability of NIBP compared to IBP, NIBP measurements as measured by the Sentinel in the manner described here are not considered as an appropriate alternative to IBP to measure blood pressure in anaesthetized horses.